The impact of trust, knowledge sharing, and affective commitment on SME innovation performance - Games, Donard; Hidayat, Tedi; Fhardilha, Jingga; Fernando, Yudi; Sari, Dessy Kurnia (Penerbit Universiti Malaysia Pahang, 2022)
Small and medium-sized enterprise (SME) performance can enhance SME sustainability and competitiveness. This study aims to examine the impacts of trust, knowledge sharing, and affective commitment on SME innovation performance. The present study will contribute to current knowledge by providing factors affecting SME innovation performance in the context of Indonesia and pandemic crises. The present study uses regression analysis by surveying 56 small business owners or managers in West Sumatra, Indonesia. It was found that trust, knowledge sharing, and affective commitment are related to SME innovation performance. Therefore, it is a moment to renew commitment to innovate by promoting trust and collaboration even during difficult situations.